CD44v6 increases gastric cancer malignant phenotype by modulating adipose stromal cell-mediated ECM remodeling. Issue 3 (16th February 2018) - Lourenço, Bianca N.; Springer, Nora L.; Ferreira, Daniel; Oliveira, Carla; Granja, Pedro L.; Fischbach, Claudia
Abstract : Biomimetic ECM models suggest that CD44v6 expression promotes fibrotic ECM remodeling and gastric cancer aggressiveness through a positive feedback mechanism. Abstract : CD44, an abundantly expressed adhesion molecule, and its alternative splice variants have been associated with tumorigenesis and metastasis. In the context of gastric cancer (GC), de novo expression of CD44 variant 6 (CD44v6) is found in more than 60% of GCs, but its role in the pathogenesis and progression of this type of cancer remains unclear. Using a combination of media conditioning experiments and decellularized extracellular matrices (ECMs), this study investigates the hypothesis that CD44v6 overexpression enhances tumor cell malignant behavior by modulating stromal cell-mediated ECM remodeling. Our findings indicate that soluble factors secreted by CD44v6 expressing GC cells particularly increase proliferation and myofibroblastic differentiation of adipose stromal cells (ASCs). These changes in ASC phenotype mediate the deposition of fibrotic/desmoplastic ECM that, in turn, stimulates GC proliferation and inhibits GC clustering. Pharmacological inhibition of matrix metalloproteinase (MMP) activity in tumor cells abrogated matrix-induced changes in tumor cell malignant behavior. Additionally, studies in mice confirmed the pathological relevance of CD44v6 expression and consequential changes in ECM remodeling to gastric tumorigenesis in vivo. Collectively, these results indicate a direct link between CD44v6, ECM remodeling, and GC malignant behavior opening new insights into potential CD44v6-targeted therapies.